The Role of supervision Quality in University Educational performance Algeria - Salima Limam; Sameer Bara; BuHaniyyah Kawi (University of Science and Technology, Yemen, 2014)
The Role of supervision Quality in University Educational performance Algeria   Abstract: Higher Education reform in Algeria following the system (Bachelor, Master, Doctorate LMD) brings new concepts stirred the university system, seeking to improve the quality of training, and to inform and guide the students; through increasing the participation of post student in building pathways configuration of the proposed offers , as well as achieving This track increase the size of personal work for the student and provide him with the skills required in the methodology and adapt to the situation. The guardianship (Tutorat) or supervision or escort is an innovation essential in the context of philosophy systems. LMD which aims to improve the quality of composition of the student informing and guidance to raise the capacity and the possibility of his participation in the construction of track formative by maximizing the volume of personal work, so the aim of this study is to address the pedagogical escort and its role in improving educational performance and according to the opinions of faculty members at Ouargla, through the distribution of a form on members of the Faculty of Law and Political Science for the detection of the importance of accompanying pedagogical and assessed for their impact on educational performance, The study concluded: that there is a close relationship between the quality of the accompanying (MCS) and the quality of higher education outputs giving the objective of the process, ithe theory, also plays a faculty member at the university a major role in improving the level of supervision and escort and ensure the quality of their output, but it remains to be the success of this operation, Faculty of Law and political science at the University of Ouargla contingent obligation of students to attend and attendance, and understand the implications and importance of the integration of the student in the world of the university and the world of work in the future, in order to achieve quality education pedagogical accompanying should be more organize and tuned, both in terms of management or understanding by the teacher, or in terms of the response students with them. Keywords: Accompanying Pedagogical, LMD system, Educational Quality.